2006
DOI: 10.1182/blood-2005-11-4385
|View full text |Cite
|
Sign up to set email alerts
|

Circulating amyloidogenic free light chains and serum N-terminal natriuretic peptide type B decrease simultaneously in association with improvement of survival in AL

Abstract: N-terminal natriuretic peptide type B (NTproBNP) is a marker of cardiac dysfunction in light chain amyloidosis (AL) and a powerful prognostic determinant. Serum NT-proBNP and circulating free light chains (FLCs) were measured at enrollment and after 3 cycles of chemotherapy in 51 patients with cardiac AL. In patients (n ‫؍‬ 22, 43%) in whom FLCs decreased by more than 50% (hematologic response), NT-proBNP concentration decreased by a median of 48%, whereas in the remaining patients it increased by 47% (P ‫؍‬ .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
166
4
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 274 publications
(179 citation statements)
references
References 18 publications
5
166
4
4
Order By: Relevance
“…One very important role of natriuretic peptides that was not addressed in the present study is monitoring improvement or progression of cardiac dysfunction after chemotherapy [4,5]. Further studies are warranted to define this role in patients with renal failure and in those in whom eGFR varies substantially during the follow-up.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…One very important role of natriuretic peptides that was not addressed in the present study is monitoring improvement or progression of cardiac dysfunction after chemotherapy [4,5]. Further studies are warranted to define this role in patients with renal failure and in those in whom eGFR varies substantially during the follow-up.…”
Section: Resultsmentioning
confidence: 90%
“…In our studies on NT-proBNP patients in dialysis were excluded [2,4,5] and, although subjects with advanced renal failure were included in the Mayo Clinic series (median creatinine 1.2 mg dL 21 , range: 0.4-14.6 mg dL 21 ), the prognostic value of NT-proBNP was not separately tested in the subgroup with renal insufficiency [3]. Thus, at present, it is uncertain whether the use of NT-proBNP as a diagnostic and prognostic marker in AL amyloidosis can be extended to patients with reduced glomerular filtration rate.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that the suppression of the synthesis of the amyloidogenic light chain translates into rapid reduction of NT-proBNP with survival benefit in the majority of patients [12]. The dramatic downhill course of patients with amyloid cardiomyopathy indicates that rapidly acting chemotherapy regimens are required to improve survival.…”
Section: Discussionmentioning
confidence: 99%
“…A >30% reduction of serum NT-proBNP concentration was considered a clinically significant improvement of cardiac dysfunction. This threshold was chosen considering the biological variability of NT-proBNP and because it was reported to translate into a survival advantage in patients with AL amyloidosis [12]. Treatment was discontinued in patients who achieved CR, in case of toxicity, or after completion of cycle 9.…”
Section: Methodsmentioning
confidence: 99%
“…42 The parallel reduction of FLC and cardiac biomarkers is associated with extended survival. 23,43 As a general rule, the deeper the hematologic response, the greater the likelihood of organ response. Occasionally, the achievement of a PR translates into a significant organ response, suggesting that the toxicity and fibrillar potential of the iFLC was dependent on a threshold concentration.…”
Section: Organmentioning
confidence: 99%